2023
DOI: 10.3390/inorganics11090366
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Hydrogen-Sensitive Pt-SnO2 Composite Nanoceramics: Contrasting Roles of Pt Nano-Catalysts Loaded via Two Different Methods

Jieting Zhao,
Jiannan Song,
Xilai Lu
et al.

Abstract: Soluble noble metal salts are widely used for loading noble metals as nano-catalysts in many applications. In this paper, Pt-SnO2 composite nanoceramics were prepared from SnO2 nanoparticles and H2PtCl6 using two Pt loading methods separately: for the solution reduction method, a H2PtCl6 solution was added to a suspension of SnO2 and zinc powder to form Pt on SnO2 nanoparticles, and for the impregnation method, Pt was formed from H2PtCl6 in the course of sintering. Although a series of samples prepared using b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…In addition, noble metals, such as Pt, Pd, and Au, have been utilized to decorate the nano metal oxides, since their catalytic effect can promote the dissociation of gas molecules and further enhance the gas-sensitive properties at room temperature [7]. Jieting Zhao et al reported that Pt-SnO 2 prepared using a solution reduction method exhibited a response of up to 9700 (resistance ratio) for 1% H 2 at room temperature [8]. Riya Wadhwa et al used Pt-modified MoS 2 flacks to achieve a significant resistivity change (23% at 50 ppm H 2 ) at low hydrogen concentrations (0.5-50 ppm) at room temperature, which the authors attributed to the Pt NPinduced H 2 spillover effect [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, noble metals, such as Pt, Pd, and Au, have been utilized to decorate the nano metal oxides, since their catalytic effect can promote the dissociation of gas molecules and further enhance the gas-sensitive properties at room temperature [7]. Jieting Zhao et al reported that Pt-SnO 2 prepared using a solution reduction method exhibited a response of up to 9700 (resistance ratio) for 1% H 2 at room temperature [8]. Riya Wadhwa et al used Pt-modified MoS 2 flacks to achieve a significant resistivity change (23% at 50 ppm H 2 ) at low hydrogen concentrations (0.5-50 ppm) at room temperature, which the authors attributed to the Pt NPinduced H 2 spillover effect [9].…”
Section: Introductionmentioning
confidence: 99%